PERUBAHAN POLA ADAPTASI MASYARAKAT MISKIN PENERIMA MANFAAT PKH DI MASA PANDEMI COVID-19 - Usman Raidar; Junaidi Junaidi (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2021)
The COVID-19 pandemic that hit the world community and even Indonesia caused various kinds of problems. This is related to how the community can adapt to the disaster, so that they are able to survive and get through it. All means are certainly done, including changing the habits they have been doing to adapt in normal times. Changes in habitual patterns in adapting are very interesting to study, especially for poor people who are beneficiaries of the hopeful family program who are certainly the most affected by this Covid-19 pandemic disaster. Therefore, it is necessary to conduct a study on how to change the adaptation pattern of the poor beneficiaries of the Family Hope Program (PKH). Of course this study uses a qualitative method with case studies. In addition, this study also uses quantitative techniques in collecting data, both in the form of primary and secondary data. This research was conducted in Bagelen Village, Gedong Tataan District, Pesawaran Regency. The results of this study, namely a change in the pattern of adaptation of the PKH beneficiary community during the Covid-19 pandemic. These changes are related to the patterns of survival carried out by PKH beneficiary communities during the Covid-19 pandemic.